P53/MicroRNA-34 axis in cancer and beyond. Issue 4 (April 2023) - Pan, Wei; Chai, Binshu; Li, Langping; Lu, Zhijun; Ma, Zhongliang
Abstract: Cancer is serious endangers human life. After a long period of research and accumulation, people's understanding of cancer and the corresponding treatment methods are constantly developing. p53 is an important tumor suppressor gene. With the more in-depth understanding of the structure and function of p53, the more importance of this tumor suppressor gene is realized in the process of inhibiting tumor formation. MicroRNAs (miRNAs) are important regulatory molecules with a length of about 22nucleotides (nt), which belong to non-coding RNA and play an important role in the occurrence and development of tumors. miR-34 is currently considered to be a master regulator of tumor suppression. The positive feedback regulatory network formed by p53 and miR-34 can inhibit the growth and metastasis of tumor cells and inhibit tumor stem cells. This review focuses on the latest progress of p5 3/miR-34 regulatory network, and discusses its application in tumor diagnosis and treatment.